The Influence Of Giving Communication, Information And Education (KIE/IEC) Toward Pregnant Woman Behavior In Implementing Genital Hygiene - Reny Nugraheni; Wahyu Sri Astutik (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Before implementing IEC, it was known that most respondents had sufficient behavior in the category of 21 respondents (56.76%) and as many as 16 respondents (43.24%) had behaviors in the less category. After implementing IEC, it is known that there was a tendency for the increase in respondent behavior, namely 33 respondents (89.19%) in the good category and 16 respondents (43.24%) of respondents had good behavior.There is an effect of giving IEC to the behavior of pregnant women in implementing genital hygiene in the Work Area of the Gurah Health Center of Kediri Regency in 2020. The need for intensive IEC giving measures to pregnant women to improve the behavior of pregnant women in the implementation of genital hygiene so as to prevent pregnant women from various problems of the impact of genital hygiene that are not implemented properly